Design and fabrication of special fixture for different weld configurations of commercial pure Titanium sheet in laser beam welding process. (December 2018) - Anthuvan Stephen Edberk, J.; Siva Shanmugam, N.; Sankaranarayanasamy, K.
Abstract: Titanium and its alloys have been used in several areas such as aerospace, automobile, marine and medical industries due to its several superior properties from other materials. In Laser Beam Welding (LBW) process, a variety of advantages such as very narrow heat affected zone, high depth to width ratio, high productivity and low residual stress are obtained. In the present study, trials were conducted in commercial pure titanium (Grade 2) material to ensure feasibility and to make different weld configuration such as lap joint and T joint in Nd: YA G single-sided during the laser beam welding process. Distortion and colorization of the welded joints were avoided by providing firm clamping and uniform shielding gas (99% pure industrial argon) using a custom-made fixtures arrangement. Hence, the quality of weld configurations of the lap joint and T joint are investigated in regard to weld morphology.